Proselytization to Polarization: The Danger(s) of (Christian) Religious Education in South Africa - Jonas Sello Thinane; Chitja Twala (E-Journal of Religious and Theological Studies)
In most African nations, including South Africa, the history of religious education is closely linked to the nation’s experience of colonization and later racial segregation under apartheid. Christian religious education in particular came to be used as a proselytizing tool through the advocacy of early Christian missionaries. In addition to such proselytization, early Christian missionaries became very instrumental in the creation and perpetuation of secular polarized higher education curricula which continue to exhibit complete submission to Euro-centric thought. The purpose of this article was thus to draw a link between historical proselytization and contemporary religious polarization visible in the religious curricula of these institutions. Methodologically, this was demonstrated, first by looking at how the spread of Christianity suppressed, marginalized, and undermined native African religious education. Second, the history of Christian religious education was presented not only as an enrichment of the Christian proselytizing program but also as a missionary tool that consolidated the polarized education that continues to shape the curriculum design of higher education systems in the countries of southern Africa. Drawing largely from secondary sources, both in history and in religious studies, the article argued that in South Africa, religious education has been used to serve the colonial and oppressive apartheid systems. The main conclusion of this article is that many curricula in South Africa’s higher education systems still reflect or are characterized by a polarized type of Euro-centric education, which is a legacy of earlier Christian proselytization initiatives.